A Case of Severe Unicuspid Aortic Valve Stenosis: Valve Repair With Tricuspidization in an Adult. (October 2015) - Tokue, Masahide; Hara, Hidehiko; Sahara, Naohiko; Yamazaki, Kenji; Yamashita, Hiromasa; Takahashi, Kei; Ozaki, Shigeyuki; Sugi, Kaoru; Nakamura, Masato
A 33-year-old male was referred to our institute with acute heart failure. The patient was found to have a unicuspid aortic valve (UAV) and severe aortic stenosis. He had been followed at a local university hospital during childhood. However, he stopped visiting the outpatient clinic after becoming an adult. His condition subsequently worsened, and he ultimately presented to our hospital with cardiogenic shock. In Japan, some adult congenital heart disease (ACHD) patients continue to be followed by pediatric cardiologists, though the patterns of practice are variable. This report describes the case of a patient who became lost to follow-up in early adulthood. We thus focus on this ACHD case as an example of the effects of inadequate communication among doctors and the need to establish better ACHD management protocols for treating this patient population.